2019
DOI: 10.3847/2041-8213/ab0ae8
|View full text |Cite|
|
Sign up to set email alerts
|

Charged Compact Binary Coalescence Signal and Electromagnetic Counterpart of Plunging Black Hole–Neutron Star Mergers

Abstract: If at least one of the members of a compact binary coalescence is charged, the inspiral of the two members would generate a Poynting flux with an increasing power, giving rise to a brief electromagnetic counterpart temporally associated with the chirp signal of the merger (with possibly a small temporal offset), which we term as the charged compact binary coalescence (cCBC) signal. We develop a general theory of cCBC for any mass and amount of charge for each member. Neutron stars (NSs), as spinning magnets, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The models invoke young pulsars (Cordes & Wasserman 2016;Connor et al 2016a), relatively old magnetars as observed (Popov & Postnov 2010;Katz 2016), putative young magnetars born from gamma-ray bursts and superluminous supernovae (SNe) (Murase et al 2016;Metzger et al 2017;Wang et al 2018), normal pulsars with external interactions (Zhang 2017), among others. The catastrophic (non-repeating) models include various types of compact star mergers, such as white dwarf (WD) -WD mergers (Kashiyama et al 2013), neutron star (NS) -NS mergers (Totani 2013;Wang et al 2016), NS -black hole (BH) mergers (Zhang 2019;Dai 2019), and even BH -BH mergers (Zhang 2016;Liu et al 2016), or collapses of supramassive neutron stars into black holes (Falcke & Rezzolla 2014;Zhang 2014). The expected event rates of these scenarios differ, and by comparing with our results, one can constrain the models.…”
Section: Constraints On the Possible Originsmentioning
confidence: 72%
“…The models invoke young pulsars (Cordes & Wasserman 2016;Connor et al 2016a), relatively old magnetars as observed (Popov & Postnov 2010;Katz 2016), putative young magnetars born from gamma-ray bursts and superluminous supernovae (SNe) (Murase et al 2016;Metzger et al 2017;Wang et al 2018), normal pulsars with external interactions (Zhang 2017), among others. The catastrophic (non-repeating) models include various types of compact star mergers, such as white dwarf (WD) -WD mergers (Kashiyama et al 2013), neutron star (NS) -NS mergers (Totani 2013;Wang et al 2016), NS -black hole (BH) mergers (Zhang 2019;Dai 2019), and even BH -BH mergers (Zhang 2016;Liu et al 2016), or collapses of supramassive neutron stars into black holes (Falcke & Rezzolla 2014;Zhang 2014). The expected event rates of these scenarios differ, and by comparing with our results, one can constrain the models.…”
Section: Constraints On the Possible Originsmentioning
confidence: 72%
“…Although most NSBH mergers are predicted to be plunging events, since the NSs are usually charged, some detectable EM signals, i.e., fast radio bursts or short-duration X-ray bursts, can be produced during the final merger phase for NSBH binaries (Zhang 2019;Dai 2019). Moreover, some CBC events are believed to be embedded in the accretion disks of active galactic nuclei (AGNs; e.g., Cheng & Wang 1999;McKernan et al 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Specifically, the tidal disruption is required to occur outside the innermost stable circular orbit of the black hole for inducing astrophysically interesting outcomes. If the neutron star is not disrupted, as is likely the case of GW200105 and GW200115, it behaves like a point particle throughout the coalescence, and the merger process will be indistinguishable from that of (highly asymmetric) binary black holes (Foucart et al 2013a) except for possible electromagnetic emission associated with crust shattering (Tsang et al 2012), magnetospheric activities (Hansen and Lyutikov 2001;McWilliams and Levin 2011;Lai 2012;Paschalidis et al 2013;D'Orazio et al 2016;Carrasco and Shibata 2020;Wada et al 2020;East et al 2021;Carrasco et al 2021, see also Ioka and Taniguchi 2000 for earlier work on binary neutron stars), or charged black holes (Levin et al 2018;Zhang 2019;Dai 2019;Pan and Yang 2019;Zhong et al 2019). These two possibilities for the fate of merger are summarized schematically in Fig.…”
mentioning
confidence: 99%